The Role of Company Size in Moderating the Effect of Profitability on Dividend Policy with Liquidity as a Control: Array - Kadek Wisnu Bhuana (JASS (Journal of Accounting for Sustainable Society), 2025)
Dividend policy is an important decision in financial management that affects shareholder welfare and the company's financial stability. In the banking industry in Indonesia, dividend policy is influenced by various factors, including profitability, liquidity and company size. This research aims to analyze the effect of profitability on dividend policy by considering company size as a moderating variable and liquidity as a control variable. Using banking data in Indonesia, the research results show that profitability has a significant influence on dividend policy, while company size strengthens this relationship. In addition, liquidity acts as a control factor that moderates financial flexibility in dividend distribution. This research contributes to understanding the factors that influence dividend policy in the banking sector and its implications for corporate financial strategies.